Transient Mild Hyperthermia Induces E-selectin Mediated Localization of Mesoporous Silicon Vectors in Solid Tumors - Kirui, Dickson K. (Public Library of Science, 2014)
BACKGROUND: Hyperthermia treatment has been explored as a strategy to overcome biological barriers that hinder effective drug delivery in solid tumors. Most studies have used mild hyperthermia treatment (MHT) to target the delivery of thermo-sensitive liposomes carriers. Others have studied its application to permeabilize tumor vessels and improve tumor interstitial transport. However, the role of MHT in altering tumor vessel interfacial and adhesion properties and its relationship to improved delivery has not been established. In the present study, we evaluated effects of MHT treatment on tumor vessel flow dynamics and expression of adhesion molecules and assessed enhancement in particle localization using mesoporous silicon vectors (MSVs). We also determined the optimal time window at which maximal accumulation occur. RESULTS: In this study, using intravital microscopy analyses, we showed that temporal mild hyperthermia (∼1 W/cm(2)) amplified delivery and accumulation of MSVs in orthotopic breast cancer tumors. The number of discoidal MSVs (1000×400 nm) adhering to tumor vasculature increased 6-fold for SUM159 tumors and 3-fold for MCF-7 breast cancer tumors. By flow chamber experiments and Western blotting, we established that a temporal increase in E-selectin expression correlated with enhanced particle accumulation. Furthermore, MHT treatment was shown to increase tumor perfusion in a time-dependent fashion. CONCLUSIONS: Our findings reveal that well-timed mild hyperthermia treatment can transiently elevate tumor transport and alter vascular adhesion properties and thereby provides a means to enhance tumor localization of non-thermally sensitive particles such as MSVs. Such enhancement in accumulation could be leveraged to increase therapeutic efficacy and reduce drug dosing in cancer therapy.